Smoking cessation at the workplace. Results of a randomised controlled intervention study. Issue 5 (1st May 2000) - Lang, T; Nicaud, V; Slama, K; Hirsch, A; Imbernon, E; Goldberg, M; Calvel, L; Desobry, P; Favre-Trosson, J P; Lhopital, C; Mathevon, P; Miara, D; et al.
Abstract : OBJECTIVES: To compare the effects of a worksite intervention by the occupational physician offering simple advice of smoking cessation with a more active strategy of advice including a "quit date" and extra support. POPULATION: Employees of an electrical and gas company seen at the annual visit by their occupational physicians. CRITERIA END POINTS: Smoking point prevalence defined as the percentage of smokers who were non-smokers at one year. Secondary criteria were the percentage of smokers who stopped smoking for more than six months and the difference in prevalence of smoking in both groups. METHODS: Randomised controlled trial. The unit of randomisation was the work site physician and a random sample of the employees of whom he or she was in charge. The length of the follow up was one year. Each of 30 work site physicians included in the study 100 to 150 employees. RESULTS: Among 504 subjects classified as smokers at baseline receiving simple advice (group A) and 591 the more active programme (group B), 68 (13.5%) in group A and 109 (18.4%) were non-smokers one year later (p=0.03; p=0.01 taking the occupational physician as the statistical unit and using a non-parametric test). Twenty three subjects (4.6%) in group A and 36 (6.1%) in group B (p=0.26) declared abstinence of six months or more. Among non-smokers at baseline, 3.4% in both groups were smokers after one year follow up. The prevalence of smokers did not differ significantly at baseline (32.9% and 32.4%, p=0.75). After the intervention the prevalence of smoking was 30.8% in group A and 28.7% in group B (p=0.19). An increase of the mean symptoms score for depression in those who quit was observed during this period. CONCLUSIONS: A simple cessation intervention strategy during a mandatory annual examination, targeting a population of smokers independently of their motivation to stop smoking or their health status, showed a 36% relative increase of the proportion of smokers who quit smoking as compared with what can be achieved through simple advice.